2009
DOI: 10.1007/s00432-009-0607-3
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1 and BRCA2 germline mutations in Korean ovarian cancer patients

Abstract: The proportion of Korean ovarian cancer patients with a strong family history was significant, and the prevalence of BRCA1 and BRCA2 mutations in such patients was high.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
60
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(73 citation statements)
references
References 32 publications
8
60
5
Order By: Relevance
“…Third, some of our Korean patients did not know the history of their family disease owing to the separation of families during the Korean War, which is the same case as a previous report. 18 Therefore, the real proportion of HNPCC in Korean patients with endometrial cancer may be higher than that of the current study. Despite these limitations, this study establishes for the first time that the BMI of patients with HNPCC related to endometrial cancer was lower than that of the patients with sporadic endometrial cancer in Korea.…”
Section: Discussioncontrasting
confidence: 60%
“…Third, some of our Korean patients did not know the history of their family disease owing to the separation of families during the Korean War, which is the same case as a previous report. 18 Therefore, the real proportion of HNPCC in Korean patients with endometrial cancer may be higher than that of the current study. Despite these limitations, this study establishes for the first time that the BMI of patients with HNPCC related to endometrial cancer was lower than that of the patients with sporadic endometrial cancer in Korea.…”
Section: Discussioncontrasting
confidence: 60%
“…The results of our analysis indicate that the 1041_1043delAGCinsT BRCA1 mutation (n = 4; 10.2%), which was repeated twice in the present study, and the 3746insA BRCA1 mutation (n = 4; 10.2%) were considered the most potential founder mutations in KoOC ( Table 5). The latter mutation was reported 3 times in Lim et al 11 and once in Kim et al 13 was not reported in the present study. In addition, the 2552delC (n = 3; 7.7%) and 509C 9 A (n = 3; 7.7%) were also considered a candidate for founder mutation.…”
Section: Resultscontrasting
confidence: 51%
“…Therefore, it is completely reproducible. This is also one of the strong merits of the study [26]. Third, we did not perform genetic testing to confirm a germline mutation.…”
Section: Discussionmentioning
confidence: 94%